PENGARUH KOMPENSASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI NEGERI SIPIL DAN PPPK DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MEDIASI - Johsan Indra Jaya; Nasrul; Sri Wiyati Mahrani; Dzulfikri Azis Muthalib (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2026)
This research is motivated by the suboptimal performance of civil servants (PNS) and government employees (PPPK) at the Cooperatives and MSMEs Office of North Konawe Regency. This is evident in low work morale, late completion of tasks, lack of initiative, and limited service innovation. These problems are thought to be influenced by unequal compensation, a bureaucratic leadership style, and differences in employee organizational commitment. This study aims to analyze the influence of compensation and leadership style on employee performance, both directly and through organizational commitment as a mediating variable. The method used is quantitative with a survey of 35 civil servants and PPPK employees. Data were collected through a Likert-scale questionnaire and analyzed using SmartPLS 4. The results show that compensation, leadership style, and organizational commitment have a positive and significant effect on employee performance. Therefore, fair compensation, participatory leadership, and strong commitment need to be considered to improve public service performance.